Proceedings of the 49th Annual ACM SIGACT Symposium on Theory of Computing 2017
DOI: 10.1145/3055399.3055450
|View full text |Cite
|
Sign up to set email alerts
|

Optimal mean-based algorithms for trace reconstruction

Abstract: In the (deletion-channel) trace reconstruction problem, there is an unknown n-bit source string x. An algorithm is given access to independent traces of x, where a trace is formed by deleting each bit of x independently with probability δ. The goal of the algorithm is to recover x exactly (with high probability), while minimizing samples (number of traces) and running time. Previously, the best known algorithm for the trace reconstruction problem was due to Holenstein et al. [SODA 2008]; it uses exp(O (n 1/2))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(141 citation statements)
references
References 13 publications
2
139
0
Order By: Relevance
“…As some points of comparison, note that there is a trivial exp(O(k/q + log n)) upper bound, which our result improves on with a polynomially better dependence on k/q in the exponent. The best known results for the general case is exp(O((n/q) 1/3 )) [11,26] and our result is a strict improvement when k = o(n/ log 2 n). Note that since we have no restrictions on k in the statement, improving upon exp(O((k/q) 1/3 )) would imply an improved bound in the general setting.…”
Section: Our Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…As some points of comparison, note that there is a trivial exp(O(k/q + log n)) upper bound, which our result improves on with a polynomially better dependence on k/q in the exponent. The best known results for the general case is exp(O((n/q) 1/3 )) [11,26] and our result is a strict improvement when k = o(n/ log 2 n). Note that since we have no restrictions on k in the statement, improving upon exp(O((k/q) 1/3 )) would imply an improved bound in the general setting.…”
Section: Our Resultssupporting
confidence: 50%
“…Additionally, our proof is constructive, and the algorithm is actually mean-based, so the only information it requires are estimates of the probabilities that each received entry is 1. As we mentioned, for the sequence case, both Nazarov and Peres [26] and De et al [11] prove a exp(Ω(n 1/3 )) lower bound for mean-based algorithms. Thus, our result provides a strict separation between matrix and sequence reconstruction, at least from the perspective of mean-based approaches.…”
Section: E S a 2 0 1mentioning
confidence: 81%
See 1 more Smart Citation
“…For the worst case scenario, in [27] it is shown that exp O(n 1/2 log n) traces suffice for reconstruction with high probability. This was later improved independently by both De, O'Donnell, and Severdio in [16] and by Nazarov and Peres [39] to exp O(n 1/3 ).…”
Section: Theoreitical Results On the Trace Reconstruction Problemmentioning
confidence: 93%
“…In fact, this setup falls under the general framework of the string reconstruction problem which refers to recovering a string based upon several noisy copies of it. Examples for this problem are the sequence reconstruction problem which was first studied by Levenshtein [34,35] and the trace reconstruction problem [4,16,26,27,43]. In general, these models assume that the information is transmitted over multiple channels, and the decoder, which observes all channel estimations, uses this inherited redundancy in order to correct the errors.…”
Section: Introductionmentioning
confidence: 99%